Ibn Hazm on Christianity: An Analysis to His Religious Approaches - Ahmad, Mahmud; Zainan Nazri, Mohd Khairul Nizam; Mat Ishak, Mardiana; Mohd Nor, Mohd Roslan; Mohd Yusuff, Mohd Yakub Zulkifli; Suliaman, Ishak; Mohd Khambali, Khadijah; Hamat, Mohd Fauzi (IDOSI, 2011)
Abstract: Ibn Hazm al-Zahiri stood out as a critical analyst of Christian scriptures, however without giving any justification (ta’lil). Thus, his analysis methodology is known as the al-Zahiri’s Methodology. This paper seeks to introduce his methodology, analyze the approaches, his objections and critiques adopted by him in his study of Christianity. The interaction between Muslims and Christians in al-Andalus (Spain) stimulated Ibn Hazm to master Christianity and its scriptures. His book al-Fasl is an outcome of the continuous friction between Islam and Christianity in al-Andalus. Kitab al-fasl fi al-milal wa al-ahwa wa al-nihal continues to be considered a work of monumental significance in comparative religion, the first of its kind to systematically study of the religious doctrines of Islam, Judaism and Christianity. Key words: Ibn Hazm % Al-Zahiri’s Methodology % Inter-religious relation % Islam % Judaism % Christianity